SEPIC Converter for Lead Acid Battery Charger Using Fuzzy Logic type-2 Controller - Moh. Ifaldi Akbar; Moh. Zaenal Efendi; Syechu Dwitya Nugraha (JAREE (Journal on Advanced Research in Electrical Engineering), 2022)
Over time, the earth where we live is getting warmer every year, this is due to the excessive use of fossil energy which is not environmentally friendly and also the greenhouse effect. Of course, this is not very good for the sustainability of our environment, with the depletion of the ozone layer on our earth, especially since Indonesia is known as a country with a tropical climate, of course, with the resulting impact, our country will be increasingly affected by the impact. In this battery charging using vrla battery and the system has a working system by utilizing a source of lighting from the sun which will be processed into a source of electricity with a solar panel, the system is designed with an output voltage of 14 vdc with an input voltage of 36 vdc from the solar panel, the voltage will be lowered through the SEPIC converter according to the value The duty cycle is set on the mosfet to charge the battery according to the calculation of load requirements. This system focuses on how to maximize battery charging using the CC-CV (constant current-constant voltage) method with a type-2 fuzzy logic algorithm and how the battery lifetime can last a relatively long time and condition switch on cc to cv on soc 99.60%.